Comparative study of cryopreservation techniques in somatic tissue of Felis silvestris catus (Research, Society and Development, 2020)
The aim of this study was to compare the effects of Slow Freezing (SF) and Solid-Surface Vitrification (SSV) on the cryopreservation of the apical ear skin of domestic cats using histological tools. Fragments of skin obtained from six cats (Felis silvestres catus) were processed and destined for cryopreservation by SF and SSV, using a solution composed of Dulbecco’s Modified Eagle Medium (DMEM) plus dimethyl sulfoxide (DMSO) at 1.5 M or 3.0 M, for SF and SSV, respectively, in addition to 0.25 M sucrose and 10% fetal bovine serum (FBS). After warming, the samples were destined for histological processing for subsequent staining with hematoxylin-eosin, Gromori trichrome, and Weigert staining, as well as the marking of nucleolus organizing regions (NORs) using silver nitrate. Thus, using the VSS technique, characteristics such as epidermis thickness, dermis, and total skin thickness, presented values similar to the control group (p > 0.05). The VSS technique proved to be efficient in maintaining the number of epidermal cells and the percentage of collagen fibers. It is concluded that the application of the VSS technique proved to be superior in the histological maintenance of the apical auricular skin of domestic cats, assisting in the generation of a somatic bank in the species.